Color lines according to the photographer Ricardo Rangel - Thompson, Drew A. (Africana Studia, 2020)
From 1932 to 1975, Portugal’s control over the colony of Mozambique hinged on an experiment with racial hierarchies. Portugal’s governing strategy led local populations to classify and organize themselves according to imposed racial categories such as white, mestiços (i.e., mixed-race), Indian, and indigena (or black). But, at the onset of increased international and local pressure that culminated with independence wars across its overseas provinces, Portugal substituted enforced distinctions with the idea of a non-racial identity. These efforts coincided, and perhaps even facilitated, the opening of commercial photography studios as well as the proliferation of photographic equipment in Mozambique. The life and work of the Mozambican press-photographer Ricardo Rangel, who started his career as a darkroom assistant, provide visual and oral records to reflect on these historical changes. To such ends, I trace Rangel’s career through the evolution of professional photography and its relationship to the contemporaneous development of Portugal’s racial politics and press censorship. First, I consider Rangel’s entry into the darkroom and the skills he acquired. Here, I highlight how the taking and viewing of photographs informed how Portugal’s racial policies unfolded in people’s daily lives. I then consider Rangel’s entry into the newsroom as a press-photographer and the editorial debates that engulfed his pictures. As his negatives, prints, and historical memories of them illustrate, Rangel did not merely insert racially marginalized groups into the visual and historical record. Aesthetic debates surfaced around Rangel’s photographs that reinforced racial divisions and determined how perceptions of race influenced the viewing and telling of Mozambique’s colonial history. Keywords: Mozambique, nationalist struggle, color lines, racial ideologies, photography, Ricardo Rangel (1924-2009), historical archiving